Leveraging HST with MUSE – I. Sodium abundance variations within the 2-Gyr-old cluster NGC 1978. Issue 3 (10th September 2020) - Saracino, S; Kamann, S; Usher, C; Bastian, N; Martocchia, S; Lardo, C; Latour, M; Cabrera-Ziri, I; Dreizler, S; Giesers, B; Husser, T-O; Kacharov, N; et al.
ABSTRACT: Nearly all of the well-studied ancient globular clusters (GCs), in the Milky Way and in nearby galaxies, show star-to-star variations in specific elements (e.g. He, C, N, O, Na, and Al), known as 'multiple populations' (MPs). However, MPs are not restricted to ancient clusters, with massive clusters down to ∼2 Gyr showing signs of chemical variations. This suggests that young and old clusters share the same formation mechanism but most of the work to date on younger clusters has focused on N variations. Initial studies even suggested that younger clusters may not host spreads in other elements beyond N (e.g. Na), calling into question whether these abundance variations share the same origin as in the older GCs. In this work, we combine Hubble Space Telescope ( HST ) photometry with Very Large Telescope (VLT)/Multi-Unit Spectroscopic Explorer (MUSE) spectroscopy of a large sample of red giant branch (RGB) stars (338) in the Large Magellanic Cloud cluster NGC 1978, the youngest globular to date with reported MPs in the form of N spreads. By combining the spectra of individual RGB stars into N-normal and N-enhanced samples, based on the 'chromosome map' derived from HST, we search for mean abundance variations. Based on the NaD line, we find a Na difference of Δ[Na/Fe] = 0.07 ± 0.01 between the populations. While this difference is smaller than typically found in ancient GCs (which may suggest a correlation with age), this result further confirms that the MP phenomenon is the same, regardless of cluster age and host galaxy. As such, these young clusters offer some of the strictest tests for theories on the origin of MPs.